Is geomorphology sleepwalking into oblivion?. Issue 5 (28th December 2014) - Woodward, Jamie
Abstract This commentary uses Google Books N‐grams to briefly explore the changing use of the word geomorphology in books published in British English and American English. Both show a decline in the use of the term geomorphology in recent years. A singular feature of the British data is a very sharp rise and fall in the use of term geomorphology in books published since 1980. The steep falling limb (post 1993) of this curve is of particular concern and several possible explanations are put forward including, since 1986, the influence exerted by Research Assessment Exercises on publication practice in UK universities. The N‐gram trends pose important questions for all geomorphologists and we should monitor them to gain a better understanding of where we need to be most visible to ensure the long‐term health of our discipline. Copyright © 2014 John Wiley & Sons, Ltd.